La didattica universitaria della storia un confronto tra Italia e Spagna - Bocchetti, Gianluca (Clio.Saggi di scienze storiche, archeologiche e storico-artistiche, 2024)
History Teaching in the university context is a completely unexplored field of research in Italy and for a large part also in those countries that can boast more solid traditions of studies in this research area. This is caused by the shared idea that the academic context is always a guarantee of a high quality of teaching. This work reverses this thesis and therefore aims to deeply investigate the teaching and learning of History to understand its effectiveness; in other words, this means understand whether and how the university can lead students to the development of Historical Thinking, i.e. the most important of the educational objectives concerning History. Through the comparison between Italy and Spain (one of the most advanced country in this research area), the use of a large variety of sources (including specific surveys) and a wide recognition of the Didactics of History as a discipline (with reference to its most important debate on Historical Thinking), the result is a first attempt to identify and analyze the original characteristics and critical issues of History in the higher education system which focuses on the most relevant disciplinary traditions, practices and teaching tools, and also on the complex relationship of academic History with school, publishing industry and digital.